Strategy To Create A Green Campus Through Sustainable Transportation According To Ui Greenmetric At Medan State Polytechnic Campus (International Journal of Architecture and Urbanism, 2024)
Medan State Polytechnic (Polmed) Polmed plans to become a green campus by 2025. This research examines Polmed's readiness in accordance with the UI GreenMetric indicators in the transportation category, by collecting primary and secondary data which is analyzed using qualitative and quantitative methods. With a land area of Â± 84,420.74 mÂ² and a total campus population of 6,748 people with a distribution of Polmed personnel and academic data, the total number of students is 6,270 people and the number of lecturers, educational staff and administrative staff is 478 people in 2022/2023, producing results research based on the UI GrreenMetric indicator that there is still low availability of environmentally friendly transportation systems in the Polmed campus area, namely the absence of an emission-free vehicle policy and the absence of initiatives to reduce private vehicles in the Polmed campus area. The program to limit or reduce parking areas on campus over the last 3 years has resulted in a reduction in parking areas of 10 - 30%. Even though pedestrian paths are available, only a few areas are said to be safe and comfortable, but are not yet friendly for people with disabilities. From the overall indicator, the score obtained was 725 out of 1,800 or 40.28% in the transportation category. To increase the percentage, efforts can be made to implement the use of electric vehicles, redesign pedestrian paths that are safe, comfortable and accessible for people with disabilities and redesign parking lots by creating multi-level parking